2001
DOI: 10.1034/j.1600-0447.2001.00017.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological functioning in chronic fatigue syndrome: a review

Abstract: The current research shows that slowed processing speed, impaired working memory and poor learning of information are the most prominent features of cognitive dysfunctioning in patients with CFS. Furthermore, to this date no specific pattern of cerebral abnormalities has been found that uniquely characterizes CFS patients. There is no overwhelming evidence that fatigue is related to cognitive performance in CFS, and researchers agree that their performance on neuropsychological tasks is unlikely to be accounte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
75
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 73 publications
(204 reference statements)
11
75
0
3
Order By: Relevance
“…As noted previously, cognitive dysfunction has been found in some, but not all, neuropsychological studies in CFS patients. For instance, whereas several investigations have shown evidence of impaired memory, attention, and information-processing speed in patients with CFS (Deluca et al, , 1997Dobbs et al, 2001;Joyce et al, 1996), other reports have failed to show any significant cognitive alterations in these patients (Michiels and Cluydts, 2001). This discrepancy between results may be due to the variability of methods of assessment of cognitive function, but also may be due to the relative presence of mental fatigue or other relevant symptoms in the patient populations examined.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…As noted previously, cognitive dysfunction has been found in some, but not all, neuropsychological studies in CFS patients. For instance, whereas several investigations have shown evidence of impaired memory, attention, and information-processing speed in patients with CFS (Deluca et al, , 1997Dobbs et al, 2001;Joyce et al, 1996), other reports have failed to show any significant cognitive alterations in these patients (Michiels and Cluydts, 2001). This discrepancy between results may be due to the variability of methods of assessment of cognitive function, but also may be due to the relative presence of mental fatigue or other relevant symptoms in the patient populations examined.…”
Section: Discussionmentioning
confidence: 93%
“…Studies have reported that 50-85% of patients with CFS report cognitive difficulties and that these contribute considerably to their social and occupational dysfunction (Christodoulou et al, 1998;Komaroff and Buchwald, 1991;Michiels and Cluydts, 2001). Neurocognitive dysfunction in patients with CFS manifests primarily in the form of concentration/attention problems, memory impairment, poor word-finding ability, decreased information-processing speed, motor slowing, and mental exhaustion (Busichio et al, 2004;Deluca et al, 2004;Michiels and Cluydts, 2001). Cognitive dysfunction in CFS patients has been found in some, but not all, objective studies (Afari and Buchwald, 2003;Michiels and Cluydts, 2001;Ross et al, 2004;Wearden and Appleby, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other findings suggest that attention could be the primary cognitive dysfunction in CFS Dickson, Toft, & O'Carroll, 2009), whereas other cognitive deficits, such as memory, could be secondary to this impairment. Overall, recent reviews conclude that the most common CFS related cognitive impairments are attention impairment (working memory and slowed reaction time) and reduced information processing speed (Cockshell & Mathias, 2010;Michiels The etiology of cognitive dysfunction in CFS is uncertain, and may have as its origin a wide spectrum of factors. One possible explanation is the effect of psychopathological factors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Neuropsychiatric impairements include the poorer performance of subjects with chronic fatigue syndrome on complex attention and information related tasks . In general, however, persons with chronic fatigue syndrome appear to possess normal cognitive and global intellectual abilities 16,17,18 Neuroendocrine studies reported that abnormalities in the hypothalamic-pituitary-adrenal (HPA) axis and serotonin pathways have been identified in chronic fatigue syndrome patients, suggesting an altered physiological response to stress . About one-third of patients with chronic fatigue syndrome have been shown to exhibit hypocortisolism , which appears to originate from a CNS source rather than a primary adrenal site 19 20,21 .…”
mentioning
confidence: 99%